2021
DOI: 10.1523/eneuro.0257-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Pubertal Differences in the Maturational Trajectories of Sleep Spindles in the Transition from Childhood to Adolescence: A Population-Based Study

Abstract: Age-related changes in sleep spindles reflect maturation of the thalamocortical network. We provide evidence that spindle metrics follow distinct developmental trajectories from each other and previously described sleep oscillations shown to index brain maturation in the transition to adolescence. Importantly, we report novel data regarding the association between spindle activity and pubertal development. Specifically, we found that less mature adolescents (86% male) experienced a greater increase in spindle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Regarding slow wave activity, previous studies reported a developmental shift in the topography from posterior to anterior areas for maximum slow wave activity, possibly reflecting the occipital to frontal pathway of cortical maturation (Feinberg et al, 2011; Kurth et al, 2010), which corresponds to the findings in the present sample of children showing the smallest age-dependent decline in slow wave activity at the frontal recording sites. Recently, evidence has been provided that age-dependent changes in slow wave activity and spindle activity might differ between girls and boys with girls showing, for example, an earlier start of the decline in slow wave activity with age than boys (Ricci, He, Calhoun, et al, 2021; Ricci, He, Fang, et al, 2021) that might be driven by the earlier pubertal development in girls. Unfortunately, we did not assess pubertal status and the uneven distribution of male and female participants in our study (with >70% of the participants being male) prevented any solid conclusions regarding sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding slow wave activity, previous studies reported a developmental shift in the topography from posterior to anterior areas for maximum slow wave activity, possibly reflecting the occipital to frontal pathway of cortical maturation (Feinberg et al, 2011; Kurth et al, 2010), which corresponds to the findings in the present sample of children showing the smallest age-dependent decline in slow wave activity at the frontal recording sites. Recently, evidence has been provided that age-dependent changes in slow wave activity and spindle activity might differ between girls and boys with girls showing, for example, an earlier start of the decline in slow wave activity with age than boys (Ricci, He, Calhoun, et al, 2021; Ricci, He, Fang, et al, 2021) that might be driven by the earlier pubertal development in girls. Unfortunately, we did not assess pubertal status and the uneven distribution of male and female participants in our study (with >70% of the participants being male) prevented any solid conclusions regarding sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the previous studies reporting decreased sleep spindle density as associated with poor cognitive outcomes; however, we did not find a significant effect of OSA severity in this association, or group differences in spindles characteristics for cognition. The association between sleep spindle activity and cognitive decline in OSA may be affected by other factors, and become more evident in clinically diagnosed patients with severe OSA and cardiovascular comorbidities (Martin et al, 2013; Mohammadi et al, 2021; Muñoz‐Torres et al, 2020; Plante et al, 2013; Ricci et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The role of sex differences in spindle characteristics remains unclear, although a few studies have reported higher spindle density in females compared with males (Huupponen et al, 2002; Purcell et al, 2017; Ricci et al, 2021; Ujma et al, 2014). In a previous study from our laboratory, we did not find sex differences in spindle density (Guadagni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of spindle characteristics, women's fast sleep spindles typically display greater density and enhanced oscillations compared to men's (Choi et al, 2019; Merikanto et al, 2017; Ricci, He, Calhoun, et al, 2021). Spectral analyses show that absolute rather than relative spectral power varies by sex, with women showing greater power densities across all frequency bands, except for Beta power, throughout the night (Yoon et al, 2021).…”
Section: Sex and Sleepmentioning
confidence: 99%